Efektivitas Model Pembelajaran Permainan Bola Edukatif Fun Ball Sign Pada Siswa Tuna Rungu di SLB YPTB-B - Laila Nur Rohmah; Luthfie Lufthansa; Ary Artanty; Nurcholis Istiawan (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
Education is a right for all individuals, including children with special needs, such as deaf students, who require a unique approach to teaching. Law Number 8 of 2016 guarantees the right to receive quality education for people with disabilities. Adaptive physical education plays a vital role in providing equal opportunities for deaf students to develop their potential, but often faces various challenges, including inappropriate teaching methodologies. This study used a quantitative approach with a pretest-posttest design to assess the effectiveness of the Fun Ball Sign learning model, which utilizes educational ball games accompanied by visual instructions. The analysis results showed a significant increase in the basic motor skills of deaf students after the implementation of the model, with an average N-Gain score in the high category. The implementation of Fun Ball Sign not only improved students' motor skills but also increased their participation, motivation, and confidence in learning. This study recommends the implementation of this model in physical education as an effective strategy to meet the learning needs of deaf students, as well as encouraging the provision of adequate facilities to support them.